A-60 Case of Moyamoya Syndrome in Haitian Female without Known Risk Factors. (30th August 2021) - Elie, Emmauela; Puentes, Gisela Aguila; Ireland, Susan; Kumbhani, Sheba
Abstract: Objective: Moyamoya is a rare, progressive cerebrovascular disorder characterized by carotid artery stenosis or occlusion. Tiny "moyamoya" blood vessels open at the brain base to compensate, often resulting in large vessel ischemic strokes or from hemorrhage of moyamoya vessels. Peak incidence in adults is 30 to 50 years old and 30% progress bilaterally. 54 year-old right-handed Black Haitian female with 13 years of education presented with new stroke, now diagnosed with bilateral moyamoya syndrome. Premorbid history includes hypertension, Type II Diabetes Mellitus, patent foramen ovale, and malignant phyllodes breast tumor treated by resection and local radiation. Presents with no traditional risk factors for moyamoya (e.g., brain radiation, sickle cell disease, neurofibromatosis). Method: Five years previously patient experienced multi-focal embolic MCA strokes from left internal carotid occlusion attributed to hypercoagulability of malignancy, returning to previous activities except driving. Present perfusion CT showed complete occlusion of bilateral cavernous carotid arteries. Diagnostic angiogram showed collateral system via PCA-MCA pial-pial collaterals in parieto-occipital-temporal regions, and leptomeningeal collaterals to ACA territory. She underwent bilateral STA-MCA direct bypass. Results: Acute neuropsychological testing conducted in Haitian Creole by native-speaking trainee showed expressive aphasia, orientation to person and situation, ability to follow 1-step commands, moderately impaired naming of familiar objects, reduced sustained attention. Also left hemiparesis, right gaze preference, and left homonymous hemianopsia. Conclusions: The present case study delineates development of secondary moyamoya in a Black Haitian woman without known risk factors, resulting in significant cognitive-linguistic deficits consistent with brain findings. Limitations include lack of validated measures in Haitian Creole.